Instilling Student Discipline Through Islamic Religious Education Activities: Menanamkan Kedisiplinan Siswa Melalui Kegiatan Pendidikan Agama Islam - Bachtiar, Yusuf; Salim, Hakimuddin (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Character education remains a pivotal aspect of holistic student development. Specific Background: In Indonesian Islamic schools, Islamic Religious Education (PAI) is instrumental in shaping discipline through structured religious routines. Knowledge Gap: However, limited studies deeply explore the sustainable role of PAI in cultivating discipline as a lived moral habit rather than mere curriculum content. Aims: This study aims to investigate how PAI contributes to instilling students’ disciplinary character through integrated religious activities in the school setting. Results: Employing a qualitative descriptive method at SMP Muhammadiyah 7 Banyudono Special Program, data from observations, interviews, and documentation revealed that discipline is nurtured through daily practices such as congregational prayer, Qur'an memorization, and surah recitation. Novelty: The study highlights the proactive role of PAI teachers—not only as instructors but as moral exemplars and consistent mentors—supported by school leadership that fosters a culture of discipline. Implications: These findings underscore that PAI-based discipline formation goes beyond theoretical teaching, embedding moral values into students’ habitual behaviors, with implications for character education frameworks in Islamic schooling contexts. Highlight PAI shapes discipline through daily religious routines. Teachers act as moral role models and mentors. School leadership reinforces a disciplined environment. Keywords: Islamic Religious Education, Student Character, Discipline Formation, Moral Habituation, School Culture